Cyber Security: Power and Technology - Lehto, Martti; Neittaanmäki, Pekka; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book gathers the latest research results of scientists from different countries who have made essential contributions to the novel analysis of cyber security. Addressing open problems in the cyber world, the book consists of two parts. Part I focuses on cyber operations as a new tool in global security policy, while Part II focuses on new cyber security technologies when building cyber power capabilities. The topics discussed include strategic perspectives on cyber security and cyber warfare, cyber security implementation, strategic communication, trusted computing, password cracking, systems security and network security among others.
I Cyber Power -- 1 Developing Political Response Framework to Cyber Hostilities -- 2 The modern strategies in the cyber warfare -- 3 Cyber Security Strategy Implementation Architecture in a Value System -- 4 Jedis and Starmen - Cyber in the Service of the Light Side of the Force -- 5 Junk information in hybrid warfare - The rhizomatic speed of social media in the spamosphere -- II Cyber in the Service of the Light Side of the Force -- 6 Real-time application-layer DDoS attacks detection in encrypted traffic -- 7 Domain Generation Algorithms (DGA) detection using machine learning methods -- 8 Tailorable Representation of Security Control Catalog on Semantic Wiki -- 9 Password Cracking -- 10 Game Console attacking -- 11 OS Attacks -- 12 Honeypot utilization for network intrusion detection -- 13 Testing framework for intrusion detection systems in encrypted traffic -- 14 Security Challenges of IoT-based Smart Home Appliances.
Keywords: Telecommunication; Data protection; Computer science; Electronic data processing -- Management; Communications Engineering, Networks; Data and Information Security; Models of Computation; IT Operations